Bioavailability of Antioxidant Vitamins in Selected Indigeneous Vegetables and their Potential use in Management of HIV/AIDS in Butula, Busia, Kenya - , Rachel Wanjiru Nambafu (Archives of Current Research International, 2024)
The study investigated feeding pattern of PLWHA in Butula division, determined vitamin A, C and E content and bioavailability in selected indigenous foods for use in the management of HIV and AIDS. Animal and plants foods accounted for 45.17 %, 21.9 %, 17.48 % and 73 % respectively of total foods consumed. Fresh blanched vegetables, contained high levels of β-carotene; 4000-9700µg/100g and α-tocopherol; 3000-7350µg/100g. Solar dried vegetables contained β-carotene of range 572-854µg/g DW and α-tocopherol of 281-673µg/g DW which is significantly lower (P<0.05) than fresh vegetables determined by HPLC. L-ascorbic acid content in fresh vegetables and fruits determined by redox titration ranged from 6 to 65mg/100g. Mean serum retinol, α-tocopherol and β-carotene levels were 0.937, 0.144 and 17.787µmol/l respectively determined using HPLC. CD4+ cell counts in blood determined using flow cytometer were within the normal range of 500-1500 cells/µl while the CD8+ cell count was in the range of 300-3300 cell/µl of blood. Hb was less than 12 g/dL and RDW was less than 15.2% indicating anaemia. 88.35% of the subjects had a CD4/CD8 ratio of less than 1, 9.71% had a CD4/CD8 ratio range of 2-3 and 1.94% had a ratio greater than 4.77.95% of the subjects had a normal weight, 11.81% were underweight, 8.66% were overweight and 1.57% were obese. Bioavailability in foods estimated using algorithm indicated a +2.17 change in serum β-carotene and +7.776 changes in serum α-tocopherol levels indicating that consumption of the foods would result to improving bioavailability of these nutrients in PLWHA in Butula.